Problems in conducting land management in agricultural enterprises in the process of land reform - Dorosh, Y.; Barvinskyi, A.; Kupriyanchik, I.; Kolisnyk, Hr.; Tretiachenko, D. (Land Management, Cadastre and Land Monitoring, 2020)
The analysis of the land management of agrarian enterprises in the process of land reform is carried out. A number of problems, related to the imperfection of the institutional environment of the land management and the land use of modern agro-formations, have been identified; incompleteness of economic and legal ownership relations between land owners and agricultural structures, delay in the development and adoption of normative legal acts, required for further reformation of land relations, and catastrophic reduction of the volume of land management works aimed at ensuring rational land use are among them.It is found that the most important of these problems are the absence of a scientifically substantiated and legislatively established Strategy for the formation of a rational system of land tenure and land use aimed at creating a favorable environment for sustainable rural development, the lack of the effective functioning of agricultural enterprises, and an increasing role of land management in ensuring environmentally safe use of land resources in agricultural production.The solution of the above problems implies improvement of the legal framework for regulation of land relations, in particular, regarding the legislative definition of the administrative status of the united territorial communities; demarcation of state and communal property lands; consolidation and prevention of further subdivision of agricultural land allocated for agricultural production. The necessity of the development and adoption of the National Program of Land Use and Protection, as well as the necessity of amending the Land Code of Ukraine and the Laws of Ukraine “On Land Management” and “On Land Protection” is substantiated.Keywords: agricultural enterprises, land management, rational land use, efficiency, land ownership.